THE IMPACT OF GREEN MARKETING ON CONSUMER BEHAVIOR: A STUDY OF PURCHASE PATTERNS IN PERSONAL CARE AND COSMETIC PRODUCTS IN UTTAR PRADESH, INDIA. - Dixit, Pravendra; Singh, P. B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The importance of green and eco-friendly marketing has increased in India as our country is facing environmental problems caused by increased pollution due to industrial growth and development. To avoid environmental pollution, companies have defined green marketing as a good marketing philosophy. In recent decades, researchers have observed a significant change in consumer behavior from choosing products based on their physical attributes such as size, color, taste or aroma to other important attributes such as environment and health. Today, consumer perception and attitudes have changed from gray products to green products. Their awareness of ecological marketing influences their purchasing behavior. Thus, companies have begun to utilize environmentally friendly marketing strategies and techniques by introducing more environmentally friendly products. Increased consumer awareness of the environmental crisis has forced marketers to adopt a green marketing strategy. The present study is an attempt to analyze the effect of consumer awareness of green and ecological marketing on purchasing behavior towards personal care and cosmetic products in Uttar Padesh . The purpose of this study is to explore the potential of green marketing in the cosmetics industry, which caters to the needs of everyone from newborns to teenagers. This industry produces a wide range of products that ensure beauty and youth .A study conducted on a sample of 500 consumers living in Uttar Padesh . Basic information was collected from the sample respondents using a structured questionnaire. The results of the study show that consumer awareness of green marketing has a significant impact on consumer purchasing behavior.